تعليم مهارة الكلام باللغة العربية للناطقين بغيرها: أثر استخدام الطريقة المباشرة: Teaching Speaking Skills in Arabic Language for Non-Arabic Speakers: Effects of Using Direct Method - Samah, Rosni; Isahak, Aishah (Journal of Islamic Educational Research, 2021)
Arabic language learning issues are constantly addressed by scholars and researchers. Arabic language learning has touched on various angles such as student, syllabus, learning method, reference material, teaching aids, environment and teacher. There are researchers who study past and present teaching methods. The result showed that Arabic language learning methods are still unchanged in many institutions such as schools and universities. They are still student-centered and still using a one-way translation approach from teachers only. The Arabic book is a book that throws the revolutionary ideas into the current method of learning. It attempts to introduce student-centered methods through activities and interactions by using target languages.